Commissioning Brian Cherney’s String Trio - Jaeger, David (Intersections)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 2017)
The author offers a personal account of the events that led him to commission Brian Cherney’s String Trio in 1976 for CBC Radio Music. The trio was first heard on the Two New Hours radio program in 1978, along with solo works for violin, viola, and cello by the German composer Bernd Alois Zimmermann. In 1979 the trio was submitted for consideration to the International Rostrum of Composers, and it was chosen as a recommended work, which resulted in the trio being broadcast in twenty-five countries, significantly enhancing Cherney’s international reputation. The performers who premiered the trio also recorded it, allowing further audiences to appreciate this important work.